MONEY NEXUS ANTARA PERKEMBANGAN FUNGSI UANG DAN DAMPAKNYA TERHADAP INFLASI DI INDONESIA - Badrudin, Rudy (Kinerja: Jurnal Bisnis dan Ekonomi, 2013)
This research was discussed about the relationship between the development of the function of money fromthe stage of barter between two commodities, which are C and Câ and then become C-M-Câ, when the moneyonce introduced. M - C - Mâ happened when the businessman utilize the money (M) to produce commodityC, that will be sell to generate more money (Mâ). Last, the trading process of M - Mâ that shown the capital orfi nancial market, just like the money or security market. The development of the function of money was shownby the changes of the money supply that weigh by the infl ation. Based on the data on 1990-2011 using theAnova and regression analysis, it is known that there were a difference between the currency money supply,demand deposits, and quasi money in Indonesia; The currency money supply didnât have signifi cantly positiveeffect on the infl ation in Indonesia; The demand deposits didnât have positive effect on the infl ation in Indonesia;and the quasi money have positive effect on the infl ation in Indonesia.Keywords: money nexus, currency money, demand deposits, quasi money, infl ation rate